KNOWLEDGE SHARING PRACTICES AND THEIR IMPACT ON POLYTECHNIC LECTURERS' JOB PERFORMANCE IN MALAYSIA: A SCOPING REVIEW. - Mad Adim, Faridzul Adzli; Syariff M. Fuad, Dayang Ragidah (International Online Journal of Education and Teaching, 2025)
Knowledge sharing is a critical component of academic success, fostering collaboration, innovation, and professional growth. In polytechnic institutions, lecturers rely on effective knowledge-sharing practices to enhance teaching methodologies, research productivity, and overall job performance. This review article examines existing literature on knowledge-sharing behaviours among Malaysian polytechnic lecturers, highlighting key factors that influence their willingness to share knowledge, such as organizational culture, leadership support, and technological integration. The objective of this review is to synthesize theoretical perspectives and empirical findings on the relationship between knowledge sharing and job performance. Using a systematic approach, relevant peer-reviewed journal articles, reports, and case studies were analysed to identify common trends, challenges, and opportunities in knowledge-sharing practices within polytechnic education. The review draws upon frameworks such as the Social Exchange Theory, the Theory of Planned Behaviour, and the Knowledge-Based View to explain the dynamics of knowledge sharing in academic institutions. Findings indicate that while knowledge-sharing practices positively impact lecturers’ teaching effectiveness, research collaboration, and professional development, several barriers persist. These include lack of trust, time constraints, inadequate institutional incentives, and limited access to digital platforms. Strategies such as fostering a knowledge-sharing culture, implementing digital repositories, and incentivizing collaborative efforts are recommended to enhance knowledge exchange and optimize job performance. This review underscores the need for more empirical research on knowledge-sharing interventions tailored to Malaysian polytechnic institutions. Strengthening these practices can significantly contribute to institutional excellence and lecturers’ career progression, ultimately benefiting students and the broader educational landscape